An Interreligious Funeral for a Taiwanese Centenarian and the Mystery of Useless Suffering (Homiletic, 2016)
Interreligious ritual and Christian preaching within it often devolve into generic theological expression. Liturgical attempts to share hospitality, unity-in-difference, and love of God end up clouding the distinctive and illuminating features of neighboring religious traditions and shrouding Christian particularity. Yet even when efforts falter to convey the love of God and neighbor with theological clarity, identifiable holiness that outshines human ingenuity can still pierce through the most opaque of prayers, ritual, and homiletic practices. In the essay below, the author engages Tom Long, Don Seaman, and John McClure, with focus upon the Levinasian idea of “useless suffering,” to explore how messianic healing became believable in the difficulties and insufficiencies of his Asian American Buddhist grandfather’s funeral and plausible for other contexts of mourning more tragic and profound.